Reduced graphene oxide doped predominantly with CF2 groups as a superior anode material for long-life lithium-ion batteries. Issue 22 (7th February 2018) - An, Haoran; Li, Yu; Feng, Yiyu; Cao, Yu; Cao, Chen; Long, Peng; Li, Shuangwen; Feng, Wei
Abstract : A fluorine-doped reduced graphene oxide (F-rGO), doped predominantly with CF2 groups, was synthesized through a solvothermal process, and applied as the anode material in a lithium-ion battery. Abstract : A fluorine-doped reduced graphene oxide (F-rGO), predominantly in the form of CF2 groups, was synthesized using the reduced-graphene-oxide precursor devoid of residual hydroxyl and carboxyl groups through a solvothermal process. The vacancies and defects accompanying the formation of the highly stable and electrochemically inert CF2 groups contribute to the excellent cycling stability of F-rGO, when it is applied as the anode material in a lithium-ion battery.